PENGEMBANGAN MODUL EKSTRAKURIKULER ISLAMIC WEAR EXHIBITION (IWE) DI PONDOK PESANTREN AL-ROSYID BOJONEGORO - Nindi Marinta Nurrahma; Lutfiyah Hidayati (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The extracurricular module has an important role in the learning activities of the Islamic Wear Exhibition (IWE) extracurricular program and can influence the learning process and learning outcomes of the Islamic Wear Exhibition (IWE) extracurricular activities. This study aims to (1) describe the validity level of the Islamic Wear Exhibition (IWE) extracurricular module at Pondok Pesantren Al-Rosyid and (2) describe the learning outcomes of students participating in the Islamic Wear Exhibition (IWE) extracurricular program at Pondok Pesantren Al-Rosyid. This study is a Research and Development (R&D) study using the ADDIE model. The research was conducted in the even semester of the 2025/2026 academic year at Pondok Pesantren Putri Al-Rosyid Bojonegoro with 30 research subjects. The instruments used in this study were module media validation sheets and learning outcomes assessment sheets. The data analysis technique used was descriptive quantitative analysis. The results of the study showed that (1) the validity level of the extracurricular module from the media aspect obtained an average score of 4.24, while the material aspect obtained an average score of 4.1, resulting in an overall validity average of 4.17, which was categorized as “valid”; (2) the students’ learning outcomes showed classical mastery of 96.67%, or 29 out of 30 students achieved scores above the Minimum Completeness Criteria (KKM), namely 75. Based on these results, it can be concluded that the Islamic Wear Exhibition (IWE) extracurricular learning module is appropriate for use and is able to produce very good learning mastery.